Pyogenic liver abscess: uncommon presentation - Sotto Mayor, Joana (BMJ Case Rep, 2016)
Pyogenic liver abscess is a rare entity, but it is fatal when untreated. With a peak incidence in the fifth decade of life, its early recognition and intervention are key to successful treatment and better prognosis of patients. In recent years, its approach has been enhanced by the use of percutaneous drainage, improved imaging techniques and a better microbiological characterisation, allowing for a more appropriate use of antibiotics. Clinical manifestations are variable and depend on the size of the abscess, the condition of the patient, associated diseases and possible complications. Among the most common symptoms that stand out are the pain in the upper quadrants of the abdomen, high fever, nausea and vomiting. The authors present the case of a patient who developed an atrial flutter as the initial presentation of a hepatic abscess that imagiologically mimicked a hepatic tumour.